Daun Henna untuk Penyembuhan Luka Tubuh: Studi Takhrij dan Syarah Hadis - Farah Dinia Tasman; Muhamad Yoga Firdaus; Yulianti Yulianti; Muhtar Solihin (Gunung Djati Conference Series, 2022)
This study aims to discuss henna leaves for healing body wounds through the application of takhrij and syarah hadith studies. This research method uses a qualitative approach through literature study related to contemporary analysis. The results of this study found a hadith about the use of henna leaves for wound healing with the quality status of sahih lighairihi in terms of sanad and matan. The discussion of this study concluded that the hadith about daub henna is maqbul and ma'mul bih for Islamic practice. The research is expected to provide benefits for the community and also medical experts to develop natural medicines from henna leaves.